2012
DOI: 10.1186/1472-6963-12-31
|View full text |Cite
|
Sign up to set email alerts
|

Service quality of private hospitals: The Iranian Patients' perspective

Abstract: BackgroundHighly competitive market in the private hospital industry has caused increasing pressure on them to provide services with higher quality. The aim of this study was to determine the different dimensions of the service quality in the private hospitals of Iran and evaluating the service quality from the patients' perspective.MethodsA cross-sectional study was conducted between October and November 2010 in Tehran, Iran. The study sample was composed of 983 patients randomly selected from 8 private gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
154
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(184 citation statements)
references
References 32 publications
19
154
3
8
Order By: Relevance
“…Responsiveness included the least quality gap which is different from some previous researches [19,20,25,28]. Following the responsiveness, the lowest one was in the empathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responsiveness included the least quality gap which is different from some previous researches [19,20,25,28]. Following the responsiveness, the lowest one was in the empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Result of Sharifirad et al (2012) study on clients of primary health care centers in Iran identified that the least mean quality gap and the highest one were in assurance and tangible dimensions respectively [19]. Zarei et al (2012) in their survey at private general hospitals in Iran found the highest and the lowest expectation and perception in tangibles and empathy dimensions respectively [20]. Boshoff and Gray (2004) identified that perception of quality of service positively correlate with patient satisfaction, willingness to recommend and intention to visit the hospital again [7].…”
Section: Introductionmentioning
confidence: 99%
“…Further, numerous studies shows that the SERVQUAL instrument has been widely applied by researchers in hospitals to measure customer perceptions of service quality (Irfan & Ijaz, 2011;Nekoei-Monghadam & Amiresmaili, 2011;Zarei, 2012). Robini & Mahadevappa, (2006) posits that it is the most appraised tool for assessing service quality in different settings, it is reliable and open for standard analysis that makes interpretation easy.…”
Section: Quality Gap In Health Service Delivery and The Servqual Modelmentioning
confidence: 99%
“…With regards to these discrepancies, Butt & de Run, (2010) remarked that it is highly crucial for healthcare providers to continuously observe and measure customer service expectations and perceptions. Suggestions to continuously monitor how well customers' expectations have been met are very obligatory as a form of after-delivery activities (Zarei et al, 2012).…”
Section: Service Delivery In the Ghanaian Health Sectormentioning
confidence: 99%
“…Este resultado corrobora os achados de um estudo realizado em oito hospitais privados no Teerã, todos os atributos da escala SERVQUAL também evidenciaram lacunas na qualidade do serviço, confirmadas pelo teste de Wilcoxon (ZAREI et al, 2012).…”
Section: Discussionunclassified